(untitled) (Sciences & Technologie. C, Biotechnologies, 2013)
The relationships between the earthworm’s species of Eastern Algeria and 11 soil characteristics have been investigated by test of correlation and analysis principal component (ACP).Eighteen earthworm species are identified in this preliminary study, dominated by the anecic species. Two groups emerge: the first consisted in its majority of endogeic species (Hormogaster redii, Octodrilus maghrebinus, Octolasion lacteum, Microscolex dubius) is linked to a high values of organic matter. The second is formed as a whole by the anecics (Aporrectodea trapezoides, Allolobophora chlorotica, Aporrectodea tetramammalis, Aporrectodea carochensis) and endogeics (Aporrectodea rosea, Microscolex phosphoreus, Aporrectodea caliginosa, Proctodrilus antipae), it is associated with environments less rich in sand and silt but with high values in pH and CaCO3.